Production and Characterization of Cellulose Nanofiber Slurries and Sheets for Biomedical Applications - Carter, Nicklaus; Grant, Isabelle; Dewey, Marley; Bourque, Mary; Neivandt, David J. (Frontiers in Nanotechnology, 2021)
Cellulose nanomaterials are produced employing a multitude of methodologies including electrospinning, bacterial generation, acid digestion, and a variety of mechanical defibrillation techniques; the morphology of the nanomaterial produced is specific to the production process. Feedstocks range from various forms of woody biomass, to fungi, and have a great impact on the resulting product. The mechanical defibrillation technique, such as that employed in the present work, continuously breaks down cellulose fibers suspended in water via segmentation and defibrillation through grinding and refining. The process is typically operated until a desired level of fines is achieved in the resultant slurry of cellulose nanofiber (CNF), alternatively known as cellulose nanofibril. Mechanical defibrillation processes can be built to produce several liters in a small batch system or up to tons per day in a continuous pilot scale refiner system. In the present work a continuous system was developed with the capacity to produce 14 L of cellulose nanofiber slurry with consistent specifications and in a manner compliant with GMP/GLP protocols in order to be amenable to biomedical applications. The system was constructed within an ISO class 7 cleanroom and refining was performed on bleached softwood pulp suspension in purified water. This manuscript details the continuous grinding system, the processes employed to produce cellulose nanofiber, and characterizes the resultant cellulose nanofiber slurry and sheets formed from the slurry.